Pelatihan Pembuatan Kompos dan Mikroorganisme Lokal dari Limbah Kulit Pisang di Desa Puncak Harapan Kabupaten Tapin: Training on Making Compost and Local Microorganisms from Banana Peel Waste in Puncak Harapan Village, Tapin Regency - Najwa, Nugraha Anthoni; Magfirah, Mutiarani Salsabila; Saputri, Henny Ramelan; Putri, Rizka Diandra; Prayogo, Joni Yogo; Saputra, Riza Adrianoor (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Bananas are a fruit that is widely used by the community, both eaten directly and processed. Puncak Harapan Village has a small and medium business unit that actively processes banana chips and produces production waste in the form of banana peels. This waste has not been utilized by the community even though it has many benefits. Banana peels contain micro and macronutrients that can fertilize plants. In addition, the content of banana peels supports the emergence of microbes that are good for plants. Banana peels can be used as a material for indigenous microbes which have various uses both directly and indirectly for plants. In addition, banana peels can be used as compost that is rich in micro and macronutrients that are good for plants. The purpose of implementing this activity is to train the community in making compost and indigenous microbes from banana peels. The implementation method is in the form of training on how to make compost and indigenous microbes from banana peels. After the training, the results were obtained that the Independent Learning Campus Independent Real Work Lecture of the Faculty of Agriculture, Lokpaikat District, through this training, could improve the knowledge and skills of the Puncak Harapan Village community, Lokpaikat District, Tapin Regency about making compost and Indigenous microbes from banana peels which are beneficial for agricultural progress.